Novel mechanisms of surfactants against Candida albicans growth and morphogenesis. (5th February 2015) - Yu, Qilin; Zhang, Bing; Ma, Feiyang; Jia, Chang; Xiao, Chenpeng; Zhang, Biao; Xing, Laijun; Li, Mingchun
Highlights: The surfactants inhibit C. albicans growth by inducing mitochondrial depolarization. CTAB exhibits strong inhibitory effect on C. albicans morphogenesis. The inhibitory effect on morphogenesis is attributed to abnormal organization of actin skeleton. CTAB may be used as anti- C. albicans agents in clinical practice. Abstract: Candida albicans is a common opportunistic fungal pathogen, causing not only superficial mucosal infections but also life-threatening systemic candidiasis in immune-compromised individuals. Surfactants are a kind of amphiphilic compounds implemented in a wide range of applications. Although their antimicrobial activity has been characterized, their effect on C. albicans physiology remains to be elucidated. In this study, we investigated the inhibitory effect of two representative surfactants, cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS), on C. albicans growth and morphogenesis. Both surfactants exhibited inhibitory effect on C. albicans growth. This effect was not attributed to plasma membrane (PM) damage, but was associated with mitochondrial dysfunction. Excitingly, the surfactants, especially CTAB, showed strong inhibitory effect on hyphal development (IC50 = 0.183 ppm for CTAB and 6.312 ppm for SDS) and biofilms (0.888 ppm for CTAB and 76.092 ppm for SDS). Actin staining and Hwp1-GFP localization further revealed that this inhibition is related to abnormal organization of actin skeleton and subsequent defect in polarized transport of hyphae-related factors. This study sheds a novel light on the antimicrobial mechanisms of surfactants, and suggests these agents as potential drugs against C. albicans hyphae-related infections in clinical practice.